2014
DOI: 10.1111/are.12570
|View full text |Cite
|
Sign up to set email alerts
|

Variability in microsatellite DNA markers in gynogenetic and backcross progenies obtained from ornamental (koi) carp (Cyprinus carpioL.) × goldfish (Carassius auratusL.) hybrid females

Abstract: Variability in microsatellite DNA markers in gynogenetic and backcross progenies obtained from ornamental (koi) carp (Cyprinus carpio L.) 3 goldfish (Carassius auratus L.) hybrid females Abstract Inheritance and segregation at five microsatellite loci were studied in diploid gynogenetic and triploid backcross progenies obtained from koi 9 goldfish hybrid females, which produce diploid eggs. Gynogenetic and backcross progenies were obtained from three individual hybrid females by inseminating eggs with genetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Primers for five microsatellite markers used successfully in C. carpio , C. auratus and C. carpio × C. auratus hybrids by Anil et al . () were chosen for use and were custom synthesized with a FAM fluorophore on the forward primer (Integrated DNA Technologies; https://www.idtdna.com/). The targeted loci were Mfw7 , Mfw13 , Mfw26 , Cca02 and Koi105‐106 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers for five microsatellite markers used successfully in C. carpio , C. auratus and C. carpio × C. auratus hybrids by Anil et al . () were chosen for use and were custom synthesized with a FAM fluorophore on the forward primer (Integrated DNA Technologies; https://www.idtdna.com/). The targeted loci were Mfw7 , Mfw13 , Mfw26 , Cca02 and Koi105‐106 .…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned above, it has recently been shown in studies performed in the U.S.A. that F 1 female C. carpio × C. auratus hybrids produce diploid eggs (Gomelsky et al , ). Using microsatellite markers, it has been demonstrated that these eggs contain the entire maternal genome (Anil et al , ). F 1 hybrid males at Kentucky State University have previously been found to be sterile (Gomelsky et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…However, research addressing the success and fitness of backcrossed hybrids in aquatic animals is scarce (Arnold, 1997;Edmands, 1999). Several studies of interspecific backcrosses have focused on salmon (Johnson and wright, 1986), bass (Gomelsky et al, 2004), catfish (Argue et al, 2003(Argue et al, , 2014, tilapia (Rajaee et al, 2014;Tave et al, 1990), and carp (Anil et al, 2014), which occasionally produce spontaneous polyploidy and gynogenesis progeny during the backcrossing process (Arai, 2001;Argue and Dunham, 1999;Bartley et al, 2001;Hulata, 1995Hulata, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Cherfas et al (1994) and Shimizu et al (2000) showed that the generation of diploid eggs by hybrid females results from the occurrence of premeiotic endomitosis (i.e., doubling of chromosomes without cytokinesis) in early oogenesis; the resulting tetraploid oocytes then undergo two normal, consecutive meiotic divisions. In a further study, the variability in microsatellite DNA markers was investigated in diploid gynogenetic and backcross triploid progenies obtained from F 1 koi 9 goldfish hybrid females (Anil, Gomelsky, & Schneider, 2016). When backcrossed with koi males, F 1 hybrid females produced triploid progeny without application of any physical treatments to early embryos.…”
Section: Introductionmentioning
confidence: 99%
“…When backcrossed with koi males, F 1 hybrid females produced triploid progeny without application of any physical treatments to early embryos. Genotypes of triploid backcross koi 9 goldfish hybrids demonstrated inheritance of the diploid maternal genome and a haploid paternal genome (Anil et al, 2016). In a further study, the variability in microsatellite DNA markers was investigated in diploid gynogenetic and backcross triploid progenies obtained from F 1 koi 9 goldfish hybrid females (Anil, Gomelsky, & Schneider, 2016).…”
Section: Introductionmentioning
confidence: 99%